Epispadias Repair after Failed Surgery in Childhood - Djordjevic, Miroslav; Kojovic, Vladimir; Bizic, Marta; Majstorovic, Marko; Vukadinovic, Vojkan; Korac, Gradimir; Krstic, Zoran (European Journal of Pediatric Surgery, 2013)
Introduction Redo surgery in failed epispadias presents a great challenge. Our aim was to present a radical approach for correction of penile deformities as well as urethral reconstruction in patients after failed epispadias repair.Materials and Methods Between January 2006 and January 2011, 13 patients, aged 13 to 22 years, underwent redo surgery due to failed epispadias repair in childhood. All patients presented with severe dorsal curvature and short urethra. First stage included penile disassembly technique with complete separation of corporal bodies, urethral dissection, and transposition and subtotal glans mobilization. Residual dorsal curvature was corrected by tunical incision and grafting of the defect. Short urethra was dissected and transposed ventrally with opening at the base of the penis. Penile entities were reassembled in normal anatomical relationship. Penile body was covered using available vascularized skin flaps. After 6 months, second stage was performed and included reconstruction of the penile urethra using buccal mucosa graft and scrotal hairless skin flap.Results Follow-up ranged from 12 to 60 months (mean 33 months). Acceptable outcome is achieved in all the patients. Complete penile lengthening and straightening is obtained in 10 out of 13 patients. Mild curvature is noted in three patients without consequences. Satisfactory sexual activity was reported from nine patients. One patient developed fistula that was closed after 4 months, whereas all other patients reported normal voiding with no difficulties.Conclusions Redo surgery of failed epispadias is very demanding procedure. Radical approach in these cases is necessary for complete repair of all penile deformities with satisfactory postoperative outcome.
Keywords: epispadias; redo surgery; penile disassembly